Pengaruh Financial Technology dalam Membantu Perkembangan UMKM di Indonesia - Utami, Daffa Mega; Sutisna, Reihan Muhammad; Simbolon, Sriagnes; Hamdal, Nanda Hashabul (Innovative: Journal Of Social Science Research, 2024)
In this study there is a focus on how Financial Technology has influenced the growth of small and medium enterprises (MSMEs). FinTech, short for "Financial Technology," is one of the many new products appearing on the market as a result of today's rapid technological advances. FinTech refers to the technical innovation of the financial sector; there are many types of Fintech that have practical applications; one of which is encouraging the growth of micro, small and medium enterprises.